ALGORITHM OF COMPARISON OF SPECTRAL CLOSENESS VALUES OF AXIAL DYNAMIC FORCE ON A BIT AT A DIFFERENT WIDTH OF FILTRATION WINDOW - Мойсишин, Василь Михайлович; Рис, Віталій Васильович; Борисевич, Богдан Дмитрович; Гураль, Інеса Михайлівна (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
As a result of experimental researches of change of axial dynamic force on mining holes are set, that between the width of filtration window which is used during determination of spectral closeness, and values of this closeness, there is empiric correlation dependence probability of existence of which is anymore after 0,98. The mean value of error between estimations of dispersions of experimental researches and dispersions calculated with the use of dependence is determined. According to the mean value of error whatever exceeds 10%, the interval of values VE gets out, for what value of spectral closeness are compared.